2021
DOI: 10.2322/tjsass.64.181
|View full text |Cite
|
Sign up to set email alerts
|

Jet Direction Control Using Circular Cylinder with Tangential Blowing

Abstract: We propose a tangential blowing cylinder, a type of circulation control wing, to control the direction of a jet replacing a blade or a cascade. Flow characteristics including deflection are experimentally investigated. Specifically, visualization observations, velocity distribution measurements, and the effects of momentum ratio, injection angle, and location of the cylinder on the deflection angle of the jet are analyzed. The stalling at an angle-of-attack above 20°with a single blade impedes direction contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…( 5). 14) In addition, as the waveforms of v r and jvj are almost the same for jvj > 0:2jU max j according to the preliminary experiment, it was confirmed that the influence on the deflection angle is negligible.…”
Section: Experimental Evaluationmentioning
confidence: 55%
See 1 more Smart Citation
“…( 5). 14) In addition, as the waveforms of v r and jvj are almost the same for jvj > 0:2jU max j according to the preliminary experiment, it was confirmed that the influence on the deflection angle is negligible.…”
Section: Experimental Evaluationmentioning
confidence: 55%
“…Several fundamental studies on fluidic thrust vectoring have been carried out. [11][12][13][14][15][16][17][18][19][20] Trancossi et al 21) investigated the Aerial Coanda High-Efficiency Orienting Nozzle (ACHEON) and discussed its practical application. Mason and Crowther 22) and Al-Asady and Abdullah 23) studied the directional control of a primary jet using a blowing flow applied as a secondary flow.…”
Section: Introductionmentioning
confidence: 99%